Analysis of Corporate Governance theories and their implications for Sri Lankan companies - Mendis, T. (University of Kelaniya, 2011)
During the past 02 decades various scholars, researchers and investors have demonstrated a high degree of exigency to accentuate the importance of Corporate Governance in the private sector organizations. Recent corporate scandals such as World.Com that shook the economic foundations in those countries, have reiterated the importance of enacting sound Corporate Governance practices in the private sector companies. In Sri Lanka too, several corporate entities dramatically collapsed in the recent past due to poor Corporate Governance practices causing much amusement and disgust in the investor community and the stakeholders. With the competition becoming stiff and fierce around the world, introduction of sound Corporate Governance practices has become of paramount importance. Hence this research paper which examines the various established theories such as the agency theory, stewardship theory, stakeholder theory, theories of hegemony, legal theory, Anglo-US Model, the Cadbury Code etc., critically analyses and suggests implications especially focusing on the private sector companies in Sri Lanka. This paper adopts the theoretical normative perspective and is based on the theories related to Corporate Governance. The analysis reveals that a typology of Corporate Governance theories can be developed by using 03 dimensions evincing concern for shareholders, directors‟ duties and accountabilities and the managerial capabilities of the corporate management of a company. Critical analysis further unveiled that theories and codes that were evolved in the last decade paid greater emphasis towards “Directors” than the other two dimensions. The concepts and contents discussed in these theories can easily be executed in order to enhance the degree of Corporate Governance in quoted companies in Sri Lanka. A limitation of this paper is that it focuses only on the management perspective rather than on the financial perspective, and discusses only the established theories and codes.